Eksperimental Perbandingan Kekuatan Tekan Karakteristik Beton Self Compacting Menggunakan Agregat Kasar Alami Dan Agregat Kasar Daur Ulang - Martinus Pramanata Sapeai; Johannes Adhijoso Tjondro (Politeknik Negeri Jakarta, 2020)
Utilization of recycled concrete waste as an alternative to natural coarse aggregates in this experiment is in accordance with the concept of sustainable construction. Concrete is the main material of structural elements most commonly used in general construction and has properties that are difficult to recycle by themselves naturally. Nowdays concrete innovation with the concept of self compacting (SCC) is widely used especially in high rise building and buildings with special specification. SCC has high flowability properties so that it can flow and compact themselves, but in SCC with normal quality still need compactor. The concept of making test specimens is in accordance with real conditions in the field, where aggregates do not go through a cleaning process. There are four different mix design with the required specified compressive strength of 20 MPa. Mix design 1A (natural coarse) and 1B (recycled coarse aggregates) has a maximum aggregate size 12.50 mm, and mix design 2A (natural coarse) and 2B (recycled coarse aggregates) has a maximum aggregate size 19.00 mm. This experimental results in specified compressive strength concrete for mix design 1A, 1B, 2A, and 2B as follows: 30.93 MPa, 26.21 MPa, 30.82 MPa and 27.60 MPa. Therefore, recycled concrete aggregates can be alternative to natural coarse aggregates and can also be made into concrete with the SCC concept.